PEWUJUDAN KOHESI DAN KOHERENSI PADA JURNAL REFLEKSI GURU BAHASA INDONESIA SMP DI KABUPATEN MAROS - Hasnah Lukman; Muhammad Darwis; Asriani Abbas (JURNAL ILMU BUDAYA, 2018)
Journal of learning reflection using cohesion and coherence. This study aims, describe the realization and the forefront of the principles of cohesion and coherence in the journals reflection of learning Indonesian junior high school teachers in Maros District.                    The type of qualitative research with descriptive method, data collection techniques refer and note. The study population is a whole lingual unit containing cohesion and coherence.              The results of the study show that the cohesion embodiment used is lexical cohesion (repetition and equivalence), grammatical cohesion (references and conjunctions), and coherence (causation, consequence, condition, argumentative and means-result) the cohesion used is repetition, equivalence, reference, and conjunction. As for the application of the coherence rules used by causal relationships, consequences, conditions, arguments, and means-results